Social Media Application for Recruitment Using Pythagorean Fuzzy - Krishna, Ganapavarapu Leela (Iraqi Journal of Science, 2022)
The growth of social media is now utilized all over the world. In the past several years social media is used to communicate between person for information sharing and entertainment but now social media is also used for the hiring. This work collects data through questionnaire and online dataset on the recruitment process for three social media i.e. Facebook, Twitter, and LinkedIn. Pythagorean Fuzzy Relation (PFR) is an expansion of both Fuzzy Relationship and Fuzzy Intuitionist Relationship. The Pythagorean fuzzy set is a modern conceptual structure with greater capacity to deal with imprecision rooted in decision making. So we used this technique to identify a social media containing more number of positive respondents in recruitment process. Consequently, Facebook is proved to have high positive feedback and low negative feedback than others. It is observed that time management factor has high impact as it achieves 0.4583 composite range than others. It is also analyzed that abusive factor should be taken care by social media during recruitment as it occupies high range of negative i.e. 0.20519 composition than others.